2019
DOI: 10.1039/c9sc00178f
|View full text |Cite
|
Sign up to set email alerts
|

Constructing new metal–organic frameworks with complicated ligands from “One-Pot” in situ reactions

Abstract: A “One-Pot” strategy has been developed to construct new metal–organic frameworks with complicated ligands from simple precursors by integrating organic and coordination chemistry.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
26
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 65 publications
(26 citation statements)
references
References 57 publications
0
26
0
Order By: Relevance
“…16,17,18 In addition to the interpenetrated Zr-based MOF investigated in this study, other interpenetrated Zr-based MOFs have been reported. [19][20][21][22] Among these, the UiO-66 type interpenetrated MOFs have been well known. [23][24][25][26][27][28][29] Other systems which exhibit interpenetration were found during isoreticular expansion of the linkers and have either ditopic [30][31][32][33][34] or tetratopic linkers, [35][36][37][38] which makes the relatively short tritopic linker used in this study a unique case.…”
Section: Introductionmentioning
confidence: 99%
“…16,17,18 In addition to the interpenetrated Zr-based MOF investigated in this study, other interpenetrated Zr-based MOFs have been reported. [19][20][21][22] Among these, the UiO-66 type interpenetrated MOFs have been well known. [23][24][25][26][27][28][29] Other systems which exhibit interpenetration were found during isoreticular expansion of the linkers and have either ditopic [30][31][32][33][34] or tetratopic linkers, [35][36][37][38] which makes the relatively short tritopic linker used in this study a unique case.…”
Section: Introductionmentioning
confidence: 99%
“…While the stabilities of Zr-MOFs constructed with low connection-number (5, and 4) nodes are still under debate 15,16,17,18 , 6-connection is likely the limit to keep the material stability at an acceptable level toward certain applications 19,20,21 . In a sharp contrast to the large number of Zr-MOFs based on high connection-number (above till 12) building units, only six compounds are constructed from 6connected Zr6-oxo clusters, including PCN-224 22 , PCN-777 23 (PCN, Porous Coordination Network), UMCM-309 24 (UMCM, University of Michigan Crystalline Material), the interpenetrated Zr-BTB 25 , MOF-808 19 and BUT-108 (BUT, Beijing University of Technology) 26 .…”
Section: Resultsmentioning
confidence: 99%
“…While the stabilities of Zr-MOFs constructed with low connection-number (5, and 4) nodes are still under debate 15,16,17,18 , 6-connection is likely the limit to keep the material stability at an acceptable level toward certain applications 19,20,21 . In a sharp contrast to the large number of Zr-MOFs based on high connection-number (above 8 till 12) building units, only six compounds are constructed from 6connected Zr6-oxo clusters, including PCN-224 22 , PCN-777 23 (PCN, Porous Coordination Network), UMCM-309 24 (UMCM, University of Michigan Crystalline Material), the interpenetrated Zr-BTB 25 , MOF-808 19 and BUT-108 (BUT, Beijing University of Technology) 26 .…”
Section: Resultsmentioning
confidence: 99%